ARID1A mutation sensitizes most ovarian clear cell carcinomas to BET inhibitors - Berns, Katrien; Caumanns, Joseph J.; Hijmans, E. Marielle; Gennissen, Annemiek M. C.; Severson, Tesa M.; Evers, Bastiaan; Wisman, G. Bea A.; Jan Meersma, Gert; Lieftink, Cor; Beijersbergen, Roderick L.; Itamochi, Hiroaki; van der Zee, Ate G. J.; et al. (Oncogene, 2018)
Current treatment for advanced stage ovarian clear cell cancer is severely hampered by a lack of effective systemic therapy options, leading to a poor outlook for these patients. Sequencing studies revealed that ARID1A is mutated in over 50% of ovarian clear cell carcinomas. To search for a rational approach to target ovarian clear cell cancers with ARID1A mutations, we performed kinome-centered lethality screens in a large panel of ovarian clear cell carcinoma cell lines. Using the largest OCCC cell line panel established to date, we show here that BRD2 inhibition is predominantly lethal in ARID1A mutated ovarian clear cell cancer cells. Importantly, small molecule inhibitors of the BET (bromodomain and extra terminal domain) family of proteins, to which BRD2 belongs, specifically inhibit proliferation of ARID1A mutated cell lines, both in vitro and in ovarian clear cell cancer xenografts and patient-derived xenograft models. BET inhibitors cause a reduction in the expression of multiple SWI/SNF members including ARID1B , providing a potential explanation for the observed lethal interaction with ARID1A loss. Our data indicate that BET inhibition may represent a novel treatment strategy for a subset of ARID1A mutated ovarian clear cell carcinomas.